Modulatory Effect of Limosilactobacillus fermentum grx08 on the Anti-Oxidative Stress Capacity of Liver, Heart, and Kidney in High-Fat Diet Rats - Hengxian Qu; Longfei Zhang; Xiaoxiao Liu; Yang Liu; Kaidong Mao; Guiqi Shen; Yunchao Wa; Dawei Chen; Yujun Huang; Xia Chen; Ruixia Gu (Fermentation, 2022)
To explore the modulating effect of Limosilactobacillus fermentum (L. fermentum) grx08 on anti-oxidative stress in the liver, heart, and kidney of high-fat diet in rats, a low-fat diet as a control and a high-fat diet was used to induce oxidative stress injury in rats. L. fermentum grx08 and its heat-inactivated bacteria were used to intervene. The results showed that the high-fat diet had caused oxidative stress injury in the liver, heart, and kidney of rats. L. fermentum grx08 significantly reduced the serum levels of liver, heart, and kidney injury markers (ALT, AST, LDH, CK-MB, UA, and Crea), while restoring the balance of lipid metabolism in the liver. It also enhanced the activity of antioxidant enzymes such as GSH-Px in the liver, heart, and kidney, scavenging NO radicals and reducing the content of MDA, a product of lipid peroxidation, which can regulate the anti-oxidative stress capacity of the liver, heart, and kidney to varying degrees. Among them, L. fermentum grx08 showed better modulating effect on kidney anti-oxidative stress, followed by liver, and the weakest modulating effect on heart. At the same time, L. fermentum grx08 heat-inactivated bacteria also had a partial modulatory effect as well as a similar effect profile to that of live bacteria.